Personal Finances vs. the Overall Economic Conditions: What Drives the New EU Member States’ Stock Markets? - Lolić, Ivana; Sorić, Petar; Čižmešija, Mirjana (Comparative Economic Research. Central and Eastern Europe, 2017)
This paper analyses the leading characteristics of the Consumer Confidence Index (CCI) with respect to stock market returns for 11 New EU Member States. It proposes novel CCI weights by minimizing mean squared errors from regression forecasting equations, using CCI lags as regressors. With regards to the obtained “optimal” weights, the examined countries are grouped into micro‑ and macro‑oriented clusters. A strong shift is found in the weights due to the recent recession. The micro aspects (reflecting the wealth effect) severely lose their importance in the crisis, while the consumers’ macroeconomic sentiments grow in significance and constitute a separate transmission channel.